Intuition and common sense: Self-Efficacy in interacting with patients in preclinical years - Gonçalo Manuel Marques Félix (2022)
Context: In the beginning of medical education, students' sense of self-efficacy about interacting with patients is based on their ideas and intuition. Research has paid little attention to students' "lay" sense of self-confidence regarding this interaction. Yet, self-efficacy can have a direct influence on individuals' performance and students' self-confidence about some aspects of the doctor-patient interaction might require special attention in medical education. The goals of this cross-sectional study were to assess this sense of self-efficacy in preclinical years and how it differs after a communication skills (CS) course, also investigating differences regarding individual characteristics. Methods: A group of 223 students at the end of their 1st year of medical school (G1) and another group of 245 students at the end of their 2nd year (G2) responded to the self-efficacy questionnaire (SE-12). G2 students had attended a CS course during their 2nd year. Analyses were based on group differences and variable associations. Results: G1 students' mean self-efficacy was 74.56, a value somewhat above the SE-12 scale's midpoint. G2 students' mean self-efficacy was significantly higher (M=87.94; p<0.01). Both groups reported greater self-efficacy regarding the emotional component (vs. content/structure) of the clinical interview, although some aspects of the interaction changed positions in students' self-efficacy rankings. Men exhibited significantly greater self-efficacy than women, in both G1 and G2. Previous contacts with physicians due to severe health problems were associated with greater self-efficacy but only in G2 (p=0.014). Conclusion: In the beginning of medical school, students display average self-confidence levels regarding their ability to interact with patients. A CS course can increase students' sense of self-efficacy even in preclinical years and self-confidence regarding some aspects, relative to others, can change after the course. Gender and real-life contacts with physicians due to severe medical problems can also play a role in students' sense of self-efficacy.